(untitled) (African Journal of Biomedical Research, 2023)
This study assessed the status of the liver and the kidneys following injury by alloxan monohydrate and treatment with Vernonia amygdalina (VA) and Baccharoides tenoreana (BT). Total of 30 male Albino Wistar rats assigned into 6 groups (A-F) of 5 rats per group were used. Forty-eight hours following administration of alloxan monohydrate to groups B-F rats, groups C-E were treated with VA, BT and combination of VA and BT respectively while group F rats received glibenclamide. Both groups A and B were administered distilled water. The treatments were daily for 21 days. On day 21, serum samples for determination of hepato-renal biochemical indices were collected. The liver and kidney tissues were also collected. The results indicated significantly elevated activities of ALT, ALP and levels of Creatinine and urea in group B rats (induced untreated) compared to the normal control group while the groups treated with the extracts especially VA showed significantly reduced activities and levels of the analytes when compared to those of the induced untreated group. Liver and kidney photomicrographs of induced untreated rats showed degenerations and necrosis of the hepatocytes and tubular epithelial cells respectively while those of the rats treated with the extracts appeared comparable to those of the normal control rats. Both VA and BT protected the liver and kidney against injury by alloxan monohydrate separately; however, combination of VA and BT did not offer a better protection.